Nonmetal sulfur-doped coral-like cobalt ferrite nanoparticles with enhanced magnetic properties. Issue 5 (7th January 2016) - Cao, Derang; Wang, Xicheng; Pan, Lining; Li, Hao; Jing, Panpan; Wang, Jianbo; Liu, Qingfang
Abstract : The saturation magnetization of sulfur-doped coral-like cobalt ferrite nanoparticles was improved to 81 emu g −1 via a facile and novel calcining process. Abstract : We have successfully prepared a series of sulfur-doped cobalt ferrite nanoparticles via a facile and novel calcining process in air. The technique requires neither pH regulation nor a gas atmosphere nor centrifugation nor any other supplementary reagents during the preparation process. Our various characterizations confirmed that the nonmetal sulfur element was successfully doped in the cobalt ferrite nanoparticles. As the sulfur concentration was increased, the shapes of the sulfur-doped cobalt ferrite nanoparticles changed, from compact microspheres to sparse coral-like nanoparticles. Significantly, the saturation magnetization of sulfur-doped cobalt ferrites was measured to be as high as 81 emu g −1, which is particularly different from the decreased saturation magnetization of previously reported metal element doping.